THE IMPACT OF ECONOMIC GROWTH IN HOUSING LOANS DEMAND IN ALBANIA - Iris Shahini (European Scientific Journal, ESJ, 2014)
The lack in empirical study of housing finance in emerging economies conduct me to use Albania as a case study. In countries like Albania where the macroeconomic volatilities are high the economic growth plays an important role in loan financing. The data collected were organized and prepared for analysis taking in consideration the Demand for Housing Loans as a dependent variable and money supply (M1) and economic growth as independent variables. The aim of this study centered on how Housing Loans demand in Albania during the financial crisis has behaved. In emerging economies like Albania where providing a dwelling for the citizens is not one of the government's priority, having a housing loan is almost the only alternative of purchasing a house. The problem is that the economic uncertainty especially when the living standard living, shrinks the individuals demand for borrowing funds from banks.